Impact of Care and Social Support on Wellbeing Among People Living with HIV/AIDS in Nigeria - Olayemi O Alawode; Adebola A Adedimeji; Oluwole Odutolu (Tehran University of Medical Sciences, 2010)
Background: Availability of antiretroviral therapies has transformed AIDS into a manageable chronic condition and improved well-being among people living with HIV/AIDS (PHA) in developed countries. In developing countries however, such transformations are yet to occur due to socio-economic, systemic and environmental constraint. This study examined the impact of social, economic, psychological and environmental factors on health and wellbeing among PHA living in southwest Nigeria.Methods: Using qualitative participatory methodology, 50 HIV positive people, 8 health personnel and 32 care providers were interviewed to explore how care and social support affect wellbeing among PHA in view of constraints to accessing antiretroviral drugs. Analysis of data used the grounded theory (GT) approach to identify themes, which are considered crucial to the wellbeing of PHA.Results: The findings highlight several factors, apart from antiretroviral drugs, that impact the wellbeing of PHA in southwest Nigeria. These include concerns about deteriorating physical health, family and childrens welfare, pervasive stigma, financial pressures and systemic failures relating to care among others. We describe how psychosocial and social support structures can considerably contribute to improving health outcomes among them because of how they affect the functioning of immune system, self-care activities and other illness behaviours.Conclusion: We recommend that interventions should address the psychosocial, socio-economic and other systemic issues that negatively influence the wellbeing of PHA and governments need to strengthen the policy environment that empowers PHA support groups.